Evaluation of Reporting Based on Descriptional Knowledge - Moorman, P. W.; van Ginneken, A. M.; Siersema, P. D.; van der Lei, J.; van Bemmel, J. H. (Journal of the American Medical Informatics Association : JAMIA, 1995)
In an attempt to enhance the completeness and clarity of clinical narratives, the authors developed a general formalism for the entry of structured data. The objective of this study was to gain insight into the expressive power of the formalism through its use for reporting in endoscopy. Each of ten endoscopists reported twice about eight endoscopy videotapes. They produced free-text reports first, and then structured reports using this formalism. Statements in the resulting reports were compared. In total, 6.8% of the endoscopists' statements could not be expressed in structured options. Most of these statements were not due to limitations of the formalism itself. Topics mentioned in the free-text reports were described more frequently in the structured reports and, in addition, the structured reports included a greater variety of topics. Overall, increases of 83% for topics not related to abnormal findings (366 in free-text reports and 671 in structured reports) and 45% for features of abnormal findings (406 in free-text reports and 586 in structured reports) were observed. Although there was an overall information gain, features of abnormal findings were, on average, described by only half of the endoscopists. The expressive power of this formalism is promising, but general, multipurpose usage of the acquired data requires that topics be described by a larger percentage of physicians. Since this formalism led to more complete and more uniform data, additional research is justified to study how spontaneous reporting can be augmented further. The few subjects that occurred less often in structured reports suggest a possible negligence effect of structured reporting.